1999
DOI: 10.1017/s1368980099000683
|View full text |Cite
|
Sign up to set email alerts
|

Costs of a healthy diet: analysis from the UK Women's Cohort Study

Abstract: Objective: To investigate the direct and indirect cost differences associated with eating a 'healthy' or 'unhealthy' diet. Design: Analysis of data from a baseline postal questionnaire for the UK Women's Cohort Study, including a detailed food frequency questionnaire (FFQ), supplemented by a telephone interview on a sub-sample. Subjects: The first 15 191 women who responded to the questionnaire, aged 35-69 years with similar numbers of meat eaters, fish eaters and vegetarians. Results: A healthy diet indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
152
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 13 publications
9
152
3
2
Order By: Relevance
“…Some have shown that diets based on grains, sweets and fats are more affordable than diets based on lean meats, fish or fresh produce (Cade et al, 1999;Drewnowski et al, 2004). Fruit, vegetables, meat and fish contribute more to diet cost than to dietary energy, whereas grain, fats and sweets contribute more to dietary energy than to diet cost.…”
Section: Discussionmentioning
confidence: 99%
“…Some have shown that diets based on grains, sweets and fats are more affordable than diets based on lean meats, fish or fresh produce (Cade et al, 1999;Drewnowski et al, 2004). Fruit, vegetables, meat and fish contribute more to diet cost than to dietary energy, whereas grain, fats and sweets contribute more to dietary energy than to diet cost.…”
Section: Discussionmentioning
confidence: 99%
“…As this procedure gives only an approximation of actual diet costs, the results of the present study should be interpreted with caution. We note, however, that a similar methodology has been used in all previous observational studies [5][6][7][8][9][10] . , size of residential area (city with $1 million; city with ,1 million; town and village), living status (living with family; living alone; living with others), current smoking (yes; no), current alcohol drinking (yes; no), current dietary supplement use (yes; no), currently trying to lose weight (yes; no), rate of eating (very slow; relatively slow; medium; relatively fast; very fast) and energy intake (kcal day 21 , continuous).…”
Section: Discussionmentioning
confidence: 99%
“…If healthier foods cost more then so too will healthier diets, suggesting that consumers with limited financial resources might select energy-dense and nutrient-dilute diets as a means of saving money. Observational studies (albeit a limited number) on the cost of freely chosen diets have consistently shown that healthful diets are more expensive than less healthful diets [5][6][7][8][9][10] . To our knowledge, however, all studies of self-selected diets and monetary costs have been conducted in European countries, with none reported in Asian countries, including Japan.…”
mentioning
confidence: 99%
“…16 It has been shown that economic constraints lead to the consumption of less healthy diets characterized through high energy density and palatability. [17][18][19] Furthermore, Cade et al 20 showed that a high adherence to a healthy dietary pattern, calculated through the Healthy Diet Indicator, was associated with higher monetary costs. Economic constraints, and their effects on food choices, have to be taken into account for the development of dietary tools for weight gain prevention.…”
Section: Introductionmentioning
confidence: 99%